Left main coronary artery and right pulmonary vein compression by a large pulmonary artery aneurysm. Issue 4 (12th March 2004) - Decuypere, V; Delcroix, M; Budts, W
Abstract : Pulmonary artery aneurysms are uncommon and may be associated with significant morbidity and mortality. The unique combination of left main coronary artery and upper right pulmonary vein compression by a large pulmonary artery aneurysm is reported. Furthermore, the aetiology, clinical manifestations, complications, diagnostic approach, and possible therapeutic interventions are briefly discussed.